Forming of Valuable Orientations in the Process of a Professional Growth of Teachers-Musicians - Mariya Kliepar (Pedagogical Discourse, 2012)
The questions of forming of valuable orientations in the process of a professional growth of a teacher-musician are analyzed in the article.